Comprehensive ultra-high-performance liquid chromatography ﬁngerprint profiling and network pharmacology analysis for the quality assessment of Lygodium japonicum (Thunb.) Sw. - Zhiwen Duan; Haibao Qiu; Xiaoxia Liu; Fangping Zhang; Wenkai Xie; Minyou He; Dongmei Sun; Xiangdong Chen; Zhenyu Li (Journal of Traditional Chinese Medical Sciences)
Objective: To evaluate the quality of Lygodium japonicum (Thunb.) Sw. (L. japonicum, Hai Jin Sha) by comparing its components without stewed (W) and stewed (S) using ultra-high-performance liquid chromatography (UHPLC) and chemometric analysis. Additionally, network pharmacology was employed to investigate the possible mechanisms of action of L. japonicum in the urinary calculi (UC) treatment. Methods: A fingerprinting method was established to identify components through UHPLC-tandem mass spectrometry. Chemometric techniques were used to compare the L. japonicum extraction methods. Furthermore, various network pharmacological approaches were used to identify and analyze the potential targets of the identified components in relation to UC. Results: The W and S extracts were distributed into two distinct clusters. Significant differences in the levels of protocatechuic aldehyde, caffeic acid, and p-coumaric acid were observed between S and W. Network pharmacology analysis revealed that the primary targets of L. japonicum in the UC treatment were serum albumin and epidermal growth factor receptors, with potential active components including protocatechuic acid and caffeic acid. Conclusion: This study comprehensively examined the therapeutic components of L. japonicum before and after boiling, shedding light on its potential mechanisms of action in UC treatment. These findings offer valuable insights into the development and utilization of L. japonicum resources.